COLLABORATIVE ORAL ASSESSMENT: AN AUTHENTIC EVALUATION STRATEGY TO FOSTER STUDENTS’ SELF-CONFIDENCE AND INTEGRITY IN THE DIGITAL ERA (A Systematic Literature Review In Vocational Education Context) - Rina Andriani; Yuni Pantiwati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Authentic assessment is challenging in the digital era, as students often rely on search engines and AI. This study conducts a Systematic Literature Review (SLR) to explore the role of oral-based collaborative assessment in fostering student self-confidence and academic integrity, particularly in vocational education. Using the PRISMA method, 50 articles published between 2020–2024 were selected from Google Scholar, ERIC, and Scopus, supplemented by classical foundational literature. Findings indicate that oral-based collaborative assessment effectively enhances self-efficacy, strengthens accountability, and promotes honest academic behavior. These insights provide practical guidance for vocational teachers to design authentic, collaborative, and digitally adaptive assessment strategies.